(untitled) (Castilla. Estudios de Literatura, 2017)
The tendency towards a strict delimitation of literary genres, the regulatory development of a generic canon emerging in Classical period and, on the other hand, the current tendency towards a dizzying dissolution of the generic statute require a new reformulation. This article –in the same line of research what Hans Robert Jauss called "horizon of expectations" of the text– tries to find the meeting point between the autonomy of the literary work (in our case, the long poem modern) and the traditional and historical rules of the literary genres in order to understand the resistance to generic definitions of the new long poem and get closer to many texts devoid of a “horizon of expectations”. In other words, our critical approach to the long poem attempts to make this resistance to generic definitions disappear. In this paper, furthermore, this new form of lyric will be characterized by its ontological criteria and determined by its genre traits. It is finally proposed a debate about generic classification possibilities of many Hispanic and universal long poems resistant to a definition and residing on the edge of traditional genres.